Date seed extract as preservatives - Mirghani, Mohamed Elwathig Saeed; Mikail, Maryam Abimbola; Ahmed, I. A.; Abdul Karim, Mohamed Ismail; Daoud, Jamal Ibrahim (IIUM Press, 2011)
The increasing demand for minimally-processed. extended shelflife foods and rcpons of ehemical preservatives as having potential toxicity demands food manufacturers to find altcrnative snurccs of anTimicrobial compounds. Food infection and into.~ication are considered as the most common causes of foodborne dir.eases worldwide. Foodbome pathogens cau.ing these diseases find their way in foods through cros, COnTamination. improper handling and temp<;'rature abuse. Food ,poilage microorganisms. On the other hand. cause products to lose thcir quality which renders them unacceptable to consumcrs, Shon shclflife of food products because of spoilage is one of thc major problems of the food induslTy. Examples of food spoilage microorganisms include P-<f:llJO",UlW;' ''':nlgillU.m. 8acilh,,· :Wblilis. I.acrolwdlllls 51' .. StJccho,-o"'yc-es cere,'i,i"e and AS/H'I"gilltr;, lIig"I".